2014
DOI: 10.1002/ceat.201300477
|View full text |Cite
|
Sign up to set email alerts
|

Polyethersulfone/Poly(D,L‐lactide) Blend Membranes: Preparation, Characterization, and Performance

Abstract: Polyethersulfone (PES) was blended with poly(D,L-lactide) (PDLLA) to prepare asymmetric membranes using the phase inversion method. The effects of the blend ratios and poly(ethylene glycol) (PEG) as additive on the membrane structure, properties, and performance were investigated. The membranes were characterized by contact angle determination, scanning electron microscopy, porosity measurement, thermogravimetric analysis, degradation tests in compost, and dynamic tests for pure water flux and bakery product w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The resulting membrane additionally showcased a 99% retention of a L. plantarum cell suspension. 84 Yuan et al fabricated a hierarchal electrospun nanofibrous PLA membrane coated with polydopamine (PDA) combined with silver nanoparticles and fluorinated thiol hydrophobic functionalization (PLA@PDA@Ag-SR-F). 141 The resulting membranes exhibited high permeation fluxes (2664 L/m 2 •h) for a wide variety of oils and a desirable separation performance (separation efficiency of >95%) for both different oil−water mixtures and surfactant-stabilized water-in-oil emulsions.…”
Section: Poly(ε-caprolactone) (Pcl) Basedmentioning
confidence: 96%
“…The resulting membrane additionally showcased a 99% retention of a L. plantarum cell suspension. 84 Yuan et al fabricated a hierarchal electrospun nanofibrous PLA membrane coated with polydopamine (PDA) combined with silver nanoparticles and fluorinated thiol hydrophobic functionalization (PLA@PDA@Ag-SR-F). 141 The resulting membranes exhibited high permeation fluxes (2664 L/m 2 •h) for a wide variety of oils and a desirable separation performance (separation efficiency of >95%) for both different oil−water mixtures and surfactant-stabilized water-in-oil emulsions.…”
Section: Poly(ε-caprolactone) (Pcl) Basedmentioning
confidence: 96%
“…According to Tab. 2 it can be concluded that membrane technology is the most suitable method for CO 2 removal from natural gas, specially in offshore, owing to its compactness and light weight, low labor intensity, a modular design permitting easy expansion or operation at partial capacity, low maintenance (no moving parts), low energy requirements, and most importantly low cost 17–23.…”
Section: Introductionmentioning
confidence: 99%